KONSEP KANDA PAT RARE DALAM PRAKTEK KEDOKTERAN MODERN - I Nyoman Hariyasa Sanjaya (Perkumpulan Organisasi Profesi DPP Dosen Hindu Indonesia (DHI) Bekerja sama dengan Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar dan Institut Agama Hindu Negeri Tampung Penyang Palangka Raya, 2024)
The Balinese society is renowned for its highly distinctive and unique culture. This culture is intricately linked to beliefs and traditions passed down by ancestors. However, when viewed through a scientific lens, each aspect of this culture holds its own significance that can be integrated into modern medicine. One of the beliefs held by the Balinese people is the presence of four siblings accompanying every human birth, known as Kanda Pat. The tangible form of Kanda Pat consists of four elements: ari-ari (placenta), lamas (umbilical cord and fat), getih (blood), and yeh nyom (amniotic fluid). In this belief, these four components symbolize the four divine powers that always accompany the human soul (atman) from birth to death. From the perspective of modern medicine, these four elements can be applied to various modalities such as stem cells and vaccines. Thus, the assimilation of culture with modern medicine can be logically explained and poses a challenge for researchers in the future.